2018
DOI: 10.5507/bp.2018.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound with hysteroscopic and histological findings for intrauterine assessment

Abstract: Introduction. Hysteroscopy with biopsy is a common diagnostic and therapeutic method in gynaecology. Its use is preceded by ultrasound examination. The success rate of predicting intrauterine findings based on ultrasound has not been assessed in the Czech Republic for a long time. In the meantime, there have been technological improvements in ultrasound devices. Method. Patients indicated for hysteroscopy underwent ultrasound examination and their medical history was recorded. The percentage agreement between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…19 In detecting endometrial pathology in the general population, TVS demonstrated moderate diagnostic accuracy compared to hysteroscopy, findings that are consistent with that of international literature. Scientific evidence was also included [23][24][25][26][27][28][29][30][31] to check our results with the ones obtained by similar international studies. It seems that through the years HSC is taking over TVS.…”
Section: Discussionmentioning
confidence: 99%
“…19 In detecting endometrial pathology in the general population, TVS demonstrated moderate diagnostic accuracy compared to hysteroscopy, findings that are consistent with that of international literature. Scientific evidence was also included [23][24][25][26][27][28][29][30][31] to check our results with the ones obtained by similar international studies. It seems that through the years HSC is taking over TVS.…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies used a DL model to identify and classify intracavitary uterine lesions at the same time. Therefore, we built a DL model for these purposes and evaluated its diagnostic performance (identification and classification) on hysteroscopy images from women performing the exam for AUB or sonographic suspect of an intrauterine lesion, then confirmed at pathological examination [26]. To the best of our knowledge, our study may be the first study with these aims and study population in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Only a minority (1%) 17,18,19 of premenopausal patients will have premalignant or malignant disease. 20 This study identified one case of malignancy in a 53-year-old woman who was perimenopausal, which is similar to other studies.…”
Section: Discussionmentioning
confidence: 99%